Long-term trends of landscape changes in marginal areas: the example of Central Europe (Šahy, Slovakia) - František PETROVIČ; Peter VARGA; Henrich GREŽO; Vladimír FALŤAN; Ingrid BELČÁKOVÁ; Zita IZAKOVIČOVÁ; Ivo MACHAR (Journal of Central European Agriculture)
The article presents changes in land use in the marginalized area of Šahy town on the Slovak-Hungarian border in relation to socio-economic changes. The aim of the research was to outline future development trends and propose management measures for the future in terms of the optimal functioning of this area. The assessment of the historical development of the landscape is based on the natural potential of the landscape, to which relevant socio-economic characteristics are added. These create and characterize the theoretical basis of the processed issue and the methodological concept for further processing. Analyses of the development and use of the landscape in the context of the real development of the landscape according to historical time horizons from the first military mapping (1769 - 1784) to the present state are conditioned by field research. Changes in land use are observed through the analysis of elements of the secondary landscape structure (SLS) and further processed methods of geographic information systems (GIS) and statistical evaluation of data. The evaluated changes are typical for the entire territory of the post-communist countries of Central Europe. They include peripheral regions in terms of environmental preservation depending on urban infrastructure. One of the conclusions of the research is the proposals for management measures for the Šahy town in connection with its strategic planning and strategic documents. The measures are divided into 3 areas - economic, social and environmental. We have determined positive or low in relation to the development of the country in the future.